Original paperDetermination of dermatology life quality index, and serum C-reactive protein and plasma interleukin-6 levels in patients with chronic urticaria - Ucmak, Derya; Akkurt, Meltem; Toprak, Gülten; Yesilova, Yavuz; Turan, Enver; Yildiz, Ismail (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: C-reactive protein (CRP) and interleukin-6 (IL-6), which is one of its most important simulators, were determined in great amounts in the sera of patients with chronic urticaria (CU). Aim: To determine the levels of IL-6 in patients with urticaria, and evaluate its relationship with urticaria activity scores and Dermatology Life Quality Index (DLQI). Material and methods : Fifty-three patients with CU were included in the study successively by determining their urticaria activity scores (0-3) and DLQI (0-5). The CRP and IL-6 were measured by immune assay methods. Thirty-two healthy subjects were included as a control group. Results : Serum levels of IL-6 and CRP were significantly higher in patients with CU compared to healthy controls (p < 0.001, p = 0.026 respectively). There was a statistically significant correlation among urticaria activity scores and IL-6 and CRP concentration (p = 0.004, p = 0.042). This correlation was more significant in patients who had moderate and severe disease activity scores than in those who had mild disease activity score (p < 0.001, p < 0.001, respectively). There was a statistically significant association between DLQI and IL-6 (p = 0.025). This correlation was very significant in patients who had severe and very severe disease activity scores (p < 0.001, p < 0.001, respectively). DLQI scores and serum levels of IL-6 were significantly different in the very severe group compared to healthy controls (p = 0.024). Conclusions : The levels of CRP and IL-6 are increased in patients with CU. A relationship of DLQI and urticaria activity scores with CRP and IL-6 was found. These findings support the relationship between the inflammatory process in CU and the clinical findings.